EP1330 Fascia closure technique using BERCI© instrument for preventing trocar-site hernia after robot-assisted gynecologic surgery. (1st November 2019) - Lee, EJ; Kim, HS; Yim, GW; Kim, JW; Park, NH
Abstract : Introduction/Background: We introduce fascia closure technique using BERCI© instrument after robot-assisted gynecologic surgery, which is necessary for management and prevention of trocar site hernia. We design a step-by-step explanation of the procedure using a video. Totally 4 trocars were inserted, including 12 mm sized umbilical trocar, bilateral 8 mm sized robot arm trocar, and 5 mm sized extra-trocar for assistant. Methodology: This video presents a systemic approach to fascia closure clearly devided into 5 steps after the main operation: (1) Right lateral trocar site fascia was closed first with BERCI© Instrument. Then, Umbilicus, left lateral, assistant port were remained. (2) Vicryl suture was inserted with BERCI© Instrument. (3) Hanging Vicryl suture on the left lateral trocar site, camera was moved from umbilical trocar to left lateral trocar site without trocar. (4) Watching the umbilical trocar site via camera, fascia was closed in the same way with BERCI© Instrument. (5) Finally, removing the camera, Vicryl suture was pulled out and tied on left lateral trocar site. All trocar site fascia was closed. At every step, it is necessary that kelly was inserted in each fascia to check Vicryl suture both sides of fascia. Results: The procedure was performed without any complications. The patient had an uneventful postoperative course and was discharged home after routine postoperative care. Since then, she showed no evidence of trocar site hernia and doing well. Conclusion: Fascia closure technique using BERCI© Instrument after robot-assisted gynecologic surgery is very safe and certain way because fascia was sutured watching with laparoscopic camera. The patient presented by us is an example showing that BERCI© Instrument can be used in the suture of trocar site. The key point in this procedure is to completely closure of fascia of trocar insertion site compared with conventional technique which is blind closure technique, so certain way to prevent trocar site hernia. Disclosure: Nothing to disclose